Matrix Metalloproteinase MMP-12 Promotes Macrophage Transmigration Across Intestinal Epithelial Tight Junctions and Increases Severity of Experimental Colitis. (9th April 2021) - Nighot, Meghali; Ganapathy, Ashwinkumar Subramenium; Saha, Kushal; Suchanec, Eric; Castillo, Eliseo F; Gregory, Alyssa; Shapiro, Steven; Ma, Thomas; Nighot, Prashant
Abstract: Background and Aims: Matrix metalloproteinases [MMPs] play an important role in extracellular matrix regulation during cell growth and wound healing. Increased expression of MMP-12 [human macrophage elastase] has been reported in inflammatory bowel disease [IBD] which is characterised by the loss of epithelial tight junction [TJ] barrier function and an excessive inflammatory response. The aim of this study was to investigate the role of MMP-12 in intestinal TJ barrier function and inflammation. Methods: Wild type [WT] and MMP-12 -/- mice were subjected to experimental acute or chronic dextran sodium sulphate [DSS] colitis. The mouse colonic permeability was measured in vivo by recycling perfusion of the entire colon and ex vivo by Ussing chamber studies. Results: DSS administration increased colonic permeability through modulation of TJ proteins and also increased MMP-12 expression in the colonic mucosa of WT mice. The acute as well as chronic DSS-induced increase in colonic TJ permeability and the severity of DSS colitis was found to be markedly attenuated in MMP-12 -/- mice. The resistance of MMP-12 -/- mice to DSS colitis was characterised by reduced macrophage infiltration and transmigration, and reduced basement membrane laminin degradation. Further in vitro and in vivo studies show that macrophage transmigration across the epithelial layer is MMP-12 dependent and the epithelial TJ barrier is compromised during macrophage transmigration. Conclusions : Together, these data demonstrate that MMP-12 mediated degradation of basement membrane laminin, macrophage transmigration, and associated loss of intestinal TJ barrier are key pathogenic factors for intestinal inflammation.